The history boys - Griffiths, Richard, 1947-2013; De la Tour, Frances, 1944-; Merrison, Clive; Jones, Damian, 1964-; Loader, Kevin; Bennett, Alan, 1934-; Moore, Stephen Campbell; Hytner, Nicholas; Fox Searchlight Pictures; DNA Films; BBC Two Films; UK Film Council; et al. ([S.l.] : 20th Century Fox Home Entertainment, 2007)
Centers around eight boisterous-yet-talented schoolboys hoping to gain admittance to England's most prestigious universities. They are aided on their quest by two teachers, a shrewd young upstart and an inspiring old eccentric, whose opposing philosophies challenge the boys to confront the true meaning of education and the relative values of happiness and success.
Special features: Audio Commentary with director Nicholas Hytner and writer Alan Bennett -- Pass it on: The history boys on screen -- History boys around the world: tour diaries.
Soundtrack album available on Koroba Records/Warner Music.
Originally released as a motion picture in 2006.
Photography, Andrew Dunn ; editor, John Wilson ; music, George Fenton ; costume designer, Justine Luxton ; production designer, John Beard.
Richard Griffiths, Frances de la Tour, Stephen Campbell Moore, Clive Merrison.
DVD; Dolby 5.1 Surround.
In English with optional English subtitles.
Keywords: High school students -- Drama; Teacher-student relationships -- England -- Drama; Feature films; Comedy films; Fiction films